Poly(2-Hydroxyethyl Methacrylate) Hydrogels for Contact Lens Applications–A Review - Saptaji, Kushendarsyah; Iza, Nurlaely Rohmatul; Widianingrum, Sinta; Mulia, Vania Katherine; Setiawan, Iwan (UI Scholars Hub, 2021)
The emerging technology in biomedical engineering requires biocompatible materials, which are also referred to as biomaterials. For a material to be considered biocompatible, it should not interact with human tissues in a harmful way, and vice versa. Various properties of biocompatible materials, such as mechanical and optical properties, have to be considered for different biomedical applications. One of the most popular applications of biomaterials is for contact lenses. Hydrogels, specifically poly(2-hydroxyethyl methacrylate) (PHEMA) hydrogels, are among the most popular ones in ophthalmologic applications, especially in soft contact lenses. This paper reviews the use of PHEMA hydrogels as one of the important biomaterials. The possible applications, properties, and manufacturing process of PHEMA hydrogels, especially in contact lens applications, are addressed. Many studies have shown that PHEMA hydrogels possess many advantages in contact lens applications and have promising development prospects.